Sow removal in a commercial pig herd in Zimbabwe - Masaka, Lawrence; Sungirai, Marvelous; Nyamukanza, Casper; Bhondai, Chido (Springer, 2016)
A study was carried out at a 2,200 sow farrow-finisher facility in Zimbabwe to determine the main reasons for sow removal and the season when removal was most common. Data on the number of sows culled and the reasons for culling as well as mortalities was recorded weekly for a 12-month period. The culling frequency was 52.8 % (n = 1 162). Descriptive statistics indicated that reproductive problems accounted for 70.8 % (n = 823) of sow removals, death (15.6 %, n = 181), lameness (4.6 %, n = 53), miscellaneous (2.5 %, n = 29), production (2.2 %, n = 26), peripartum (2.2 %, n = 25) and age (2.2 %, n = 25). The results also showed that culling was highest in gilts and primiparous sows (41.3 %, n = 480) with the least culling being observed in sows in parity 7 (5.3 %, n = 61). The hot wet season was observed to be the one when culling was most common (33.5 %, n = 389) with the least being in the cold dry season (17 %, n = 198). It was concluded that most of the sow removal was unplanned. There is a need to improve replacement gilt selection, reproductive efficiency, health and nutrition management to increase productivity in a sow unit.